Dual role of polyglycerol vitamin E succinate in emulsions: An efficient antioxidant emulsifier. (1st August 2023) - Zhou, Yanyan; Luo, Xiang; Wang, Zhixin; McClements, David Julian; Huang, Wenna; Fu, Hongliang; Zhu, Kewu
Graphical abstract: Highlights: Polyglycerol vitamin E succinate (PG20-VES) is a promising multifunctional food additive. PG20-VES is a surface-active substance with low CMC (3.2 μg/mL) and interfacial tension (28.1 mN/m). PG20-VES can scavenge ABTS + radicals and act as an antioxidant. PG20-VES stabilized oil-in-water emulsion showed excellent physicochemical stability. Abstract: α-Tocopherol, as an oil-soluble vitamin with strong antioxidant activity. It is the most naturally abundant and biologically active form of vitamin E in humans. In this study, a novel emulsifier (PG20-VES) was synthesized by attaching hydrophilic twenty-polyglycerol (PG20) to hydrophobic vitamin E succinate (VES). This emulsifier was shown to have a relatively low critical micelle concentration (CMC = 3.2 μg/mL). The antioxidant activities and emulsification properties of PG20-VES were compared with those of a widely used commercial emulsifier: D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS). PG20-VES exhibited a lower interfacial tension, stronger emulsifying capacity and similar antioxidant property to TPGS. An in vitro digestion study showed that lipid droplets coated by PG20-VES were digested under simulated small intestine conditions. This study showed that PG20-VES is an efficient antioxidant emulsifier, which may have applications in the formulation of bioactive delivery systems in the food, supplement, and pharmaceutical industries.